Coil parts
By forming a region where Cu and Mg coexist in the glass layer of the coil module, the problems of diffusion and deposition of Cu modules are solved, the copper coating phenomenon is prevented, and the performance stability of the coil module is ensured.
Patent Information
- Application Number
- JP2022157834
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-09-30
AI Technical Summary
In a coil assembly, diffusion of Cu assembly in the glass layer may cause Cu to deposit on the outer surface of the glass layer, thereby causing copper dispersion, affecting the formation of the outer electrode and the performance of the coil assembly.
By forming a region where Cu and Mg coexist in the glass layer, the Cu component is prevented from diffusing to the outer surface of the glass layer, thereby avoiding the occurrence of copper coating.
It effectively suppresses the diffusion and deposition of Cu components, prevents the occurrence of copper coating, and ensures the performance stability of the coil components and the correct formation of the external electrodes.
Smart Images

Figure 0007647717000001 
Figure 0007647717000002 
Figure 0007647717000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a coil component. [Background technology]
[0002] Patent Document 1 discloses a coil component comprising an element body including a first glass layer, a first ferrite layer formed on a first main surface of the first glass layer, and a second ferrite layer formed on a second main surface of the first glass layer, a coil embedded in the first glass layer, and an external electrode provided on a side surface of the element body across the first ferrite layer, the first glass layer, and the second ferrite layer, wherein, when viewed in a plan view from a direction perpendicular to the side surface of the element body, the width of the external electrode in the ferrite layer region is larger than the width of the external electrode in the glass layer region. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-86981 Summary of the Invention [Problem to be solved by the invention]
[0004] In a coil component having a structure in which a pair of ferrite layers are arranged on both main surfaces of a glass layer in which a coil is embedded, such as the coil component described in Patent Document 1, when an unfired element is fired, the Cu component contained in the ferrite layer diffuses into the glass layer. The Cu component diffused into the glass layer may migrate to the outer surface of the glass layer when a base electrode constituting an external electrode is fired, and may precipitate on the outer surface of the glass layer. In particular, when forming a plated electrode constituting an external electrode, the Cu component precipitated on the outer surface of the glass layer may cause a defect called "plating elongation," in which the plated electrode protrudes from a target position.
[0005] The present invention has been made to solve the above problems, and has an object to provide a coil component that can suppress the migration of Cu components to the outer surface of the glass layer. [Means for solving the problem]
[0006] The coil component of the present invention comprises an element body including a laminate in which a first ferrite layer, a first glass layer, and a second ferrite layer are stacked in this order, a coil embedded inside the first glass layer, and an external electrode provided on the outer surface of the element body and electrically connected to the coil, wherein the first glass layer has an area in which Cu and Mg coexist. Effect of the Invention
[0007] According to the present invention, it is possible to provide a coil component capable of suppressing the migration of Cu components to the outer surface of the glass layer. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a perspective view illustrating an example of a coil component according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a WT cross-sectional view of the coil device shown in FIG. [Diagram 3] FIG. 3 is an exploded perspective view of the coil component (excluding the external electrodes) shown in FIG. [Figure 4] FIG. 4 is a perspective view illustrating an example of a coil component according to the second embodiment of the present invention. [Diagram 5] FIG. 5 is a WT cross-sectional view of the coil device shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The coil component of the present invention will be described below. Note that the present invention is not limited to the following configurations, and may be modified as appropriate without departing from the gist of the present invention. In addition, a combination of multiple individual preferred configurations described below also constitutes the present invention.
[0010] The following embodiments are merely examples, and it goes without saying that partial replacement or combination of the configurations shown in different embodiments is possible. From the second embodiment onwards, the description of the matters common to the first embodiment will be omitted, and the differences will be mainly described. In particular, similar effects due to similar configurations will not be mentioned one by one for each embodiment.
[0011] In the following description, unless there is a need to distinguish between the various embodiments, they will simply be referred to as "the coil component of the present invention."
[0012] In the following embodiments, a common mode choke coil is shown as an example of a coil component of the present invention. The coil component of the present invention can also be applied to coil components other than a common mode choke coil.
[0013] The drawings shown below are schematic diagrams, and the dimensions, aspect ratio, scale, etc. may differ from those of the actual product.
[0014] In this specification, terms indicating the relationship between elements (e.g., "parallel," "orthogonal," etc.) and terms indicating the shapes of elements not only mean the literal strict form, but also mean a range that is substantially equivalent, for example, a range that includes a difference of about a few percent.
[0015] [First embodiment] In the coil component according to the first embodiment of the present invention, the element body includes a laminate in which a first ferrite layer, a first glass layer, and a second ferrite layer are laminated in this order.
[0016] Fig. 1 is a perspective view showing a schematic diagram of an example of a coil component according to a first embodiment of the present invention. Fig. 2 is a WT cross-sectional view of the coil component shown in Fig. 1. Fig. 3 is an exploded perspective view of the coil component (excluding external electrodes) shown in Fig. 1.
[0017] The coil component 1 shown in Figure 1 is a so-called common mode choke coil, and includes a body 10, a coil 20 embedded inside the body 10 (see Figures 2 and 3), and an external electrode 30 provided on the outer surface of the body 10 and electrically connected to the coil 20 (see Figure 2).
[0018] In this specification, the length direction, height direction, and width direction are defined as directions L, T, and W, respectively, as shown in Fig. 1 etc. Here, the length direction L, height direction T, and width direction W are perpendicular to each other.
[0019] The element body 10 is, for example, rectangular or approximately rectangular, and has a first end face 11a and a second end face 11b facing each other in the longitudinal direction L, a first main surface 12a and a second main surface 12b facing each other in the height direction T, and a first side surface 13a and a second side surface 13b facing each other in the width direction W.
[0020] The corners and ridges of the element body 10 may be rounded. The corners of the element body 10 are parts where three faces of the element body 10 intersect. The ridges of the element body 10 are parts where two faces of the element body 10 intersect.
[0021] The element body 10 includes a laminate in which a first ferrite layer 41, a first glass layer 51, and a second ferrite layer 42 are laminated in this order. In the example shown in Fig. 1, Fig. 2, and Fig. 3, the first ferrite layer 41, the first glass layer 51, and the second ferrite layer 42 are laminated in the height direction T.
[0022] In other words, the element body 10 includes a first glass layer 51, and a first ferrite layer 41 and a second ferrite layer 42 that sandwich the first glass layer 51 in the stacking direction (here, the height direction T). That is, in the stacking direction (here, the height direction T), the first ferrite layer 41 is disposed on one main surface of the first glass layer 51, and the second ferrite layer 42 is disposed on the other main surface of the first glass layer 51.
[0023] The first glass layer 51 has a region 55 (see FIG. 2) where Cu and Mg coexist. In the present disclosure, the state where Cu and Mg coexist may mean that Cu and Mg are mixed and present in a region such as region 55, or that Cu and Mg are separated and present in the region. Note that the region where Cu and Mg coexist may or may not contain substances other than Cu and Mg. If the region where the Cu component exists and the region where the Mg component exists overlap in element mapping by FE-WDX described later, or are close to each other in the same region, it can be said that "Cu and Mg coexist."
[0024] When the unsintered element body 10 is fired, the Cu component contained in the first ferrite layer 41 and the second ferrite layer 42 diffuses into the first glass layer 51. However, by forming a region 55 in which Cu and Mg coexist in the first glass layer 51, the Cu component is prevented from migrating to the outer surface of the first glass layer 51. As a result, when the base electrode constituting the external electrode 30 is fired, the Cu component is prevented from precipitating on the outer surface of the first glass layer 51. Therefore, even when the plated electrode constituting the external electrode 30 is formed, the occurrence of plating elongation can be prevented.
[0025] The Cu component and the Mg component contained in the first glass layer 51 can be confirmed by element mapping by field emission wavelength-dispersive X-ray spectrometry (FE-WDX). The above element mapping can also be used to confirm the Cu component and the Mg component in the observation of the second glass layer 52 and the third glass layer 53 described later.
[0026] The regions 55 in which Cu and Mg coexist are preferably scattered in the first glass layer 51. In FIG. 2, the regions 55 in which Cu and Mg coexist are uniformly scattered in the first glass layer 51, but they may be scattered non-uniformly in the first glass layer 51.
[0027] The size, shape, and the like of the region 55 where Cu and Mg coexist are not particularly limited, but the maximum width of the region 55 where Cu and Mg coexist is preferably 5 μm or less, more preferably 4 μm or less, whereas the maximum width of the region 55 where Cu and Mg coexist is, for example, 0.5 μm or more.
[0028] The maximum width of the region 55 where Cu and Mg coexist can be measured from the size of the portion where both the Cu component and the Mg component are present in the element mapping by FE-WDX described above. As a cross section for observing the region 55 where Cu and Mg coexist, it is preferable to use a cross section (WT cross section) obtained by polishing the sample in the length direction L as shown in FIG. 1 to a depth where the approximate center of the sample in the length direction L is exposed. The same cross section may also be used for observing the second glass layer 52 and the third glass layer 53 described later.
[0029] The region 55 in which Cu and Mg coexist is preferably present near the interface between the first ferrite layer 41 and the first glass layer 51. Specifically, the region 55 in which Cu and Mg coexist is preferably present within a range of 1 / 5 of the thickness of the first glass layer 51 from the interface between the first ferrite layer 41 and the first glass layer 51, for example, within 20 μm from the interface between the first ferrite layer 41 and the first glass layer 51. Similarly, the region 55 in which Cu and Mg coexist is preferably present near the interface between the second ferrite layer 42 and the first glass layer 51. Specifically, the region 55 in which Cu and Mg coexist is preferably present within a range of 1 / 5 of the thickness of the first glass layer 51 from the interface between the second ferrite layer 42 and the first glass layer 51, for example, within 20 μm from the interface between the second ferrite layer 42 and the first glass layer 51. In addition, in a range other than the above, for example, near the center in the thickness direction of the first glass layer 51, a region 55 in which Cu and Mg coexist may or may not be present.
[0030] The first glass layer 51 contains, for example, at least B, Si, and Mg. In addition to B, Si, and Mg, the first glass layer 51 preferably further contains K. The first glass layer 51 may contain elements other than these, such as Al.
[0031] The first glass layer 51 may contain at least forsterite.
[0032] The first glass layer 51 preferably contains a glass material. The glass material contained in the first glass layer 51 preferably contains at least K, B, and Si. 2 Converted to O, 0.5% by weight or more and 5% by weight or less, B is B 2 O 3 10% by weight or more and 25% by weight or less of Si in terms of SiO 2 70% or more and 85% or less by weight, and Al is 2 O 3 It is more preferable that the content is 0% by weight or more and 5% by weight or less in terms of total weight.
[0033] The first glass layer 51 may contain a filler in addition to the glass material. In this case, the filler contained in the first glass layer 51 is forsterite (2MgO SiO 2 The filler contained in the first glass layer 51 is preferably quartz (SiO 2 ) and alumina (Al 2 O 3 In particular, the filler contained in the first glass layer 51 preferably contains quartz, alumina, and forsterite.
[0034] The first glass layer 51 is preferably made of a glass ceramic material that includes a glass material and a filler.
[0035] When the glass ceramic material contains forsterite as a filler, the glass ceramic material preferably contains forsterite in the range of 5% by volume to 15% by volume (6% by weight to 14% by weight).
[0036] When the total amount of the glass ceramic material is 100% by weight, B is 2 O 3 8% or more and 12% or less by weight, and Al is converted to Al 2 O 3 2% by weight or more and 3% by weight or less of Si in terms of SiO 2 70% by weight or more and 85% by weight or less, K is converted to K 2 It is preferable that the content be 0.5% by weight or more and 1.5% by weight or less in terms of O, and 3% by weight or more and 10% by weight or less in terms of MgO.
[0037] The thickness (dimension in the height direction T) of the first glass layer 51 is, for example, not less than 20 μm and not more than 300 μm, and preferably not less than 30 μm and not more than 200 μm.
[0038] The ferrite materials constituting the first ferrite layer 41 and the second ferrite layer 42 may be the same or different. The first ferrite layer 41 and the second ferrite layer 42 are preferably made of the same ferrite material.
[0039] The ferrite material contains, for example, Fe, Zn, Cu, and Ni as main components. In addition to the above main components, the ferrite material also contains Mn 3 O 4 , Co 3 O 4 , SnO 2 , Bi 2 O 3 , SiO 2 The ferrite material may further contain additives such as Cu. The ferrite material may further contain inevitable impurities. However, it is sufficient that the ferrite material constituting at least one of the first ferrite layer 41 and the second ferrite layer 42 contains Cu, and the ferrite material constituting the other ferrite layer may or may not contain Cu.
[0040] The ferrite material constituting the first ferrite layer 41 and the second ferrite layer 42 is Fe. 2 O 3 It is preferable that the content is 40 mol% or more and 49.5 mol% or less when calculated as Zn, 5 mol% or more and 35 mol% or less when calculated as ZnO, 6 mol% or more and 12 mol% or less when calculated as CuO, and 8 mol% or more and 40 mol% or less when calculated as NiO.
[0041] The thickness (dimension in the height direction T) of the first ferrite layer 41 may be the same as or different from the thickness (dimension in the height direction T) of the second ferrite layer 42. Furthermore, the thickness of the first ferrite layer 41 may be the same as, smaller than, or larger than the thickness of the first glass layer 51. Similarly, the thickness of the second ferrite layer 42 may be the same as, smaller than, or larger than the thickness of the first glass layer 51.
[0042] The glass layer and the ferrite layer are distinguished as follows. First, the coil component is sealed with resin as necessary, and then the coil component is polished in a first direction (e.g., length direction) perpendicular to the lamination direction (e.g., height direction) to expose a cross section along the lamination direction, a second direction (e.g., width direction) perpendicular to the lamination direction and the first direction at approximately the center of the first direction. Next, a composition (content ratio of detected elements) is obtained by scanning transmission electron microscope-energy dispersive X-ray analysis (STEM-EDX) for a region where it is estimated that different layers exist in the exposed cross section of the element body (e.g., a region where it is estimated that different layers exist due to differences in color tone, etc.). Then, the glass layer and the ferrite layer are distinguished from each other by determining whether the constituent material of each layer is a glass ceramic material or a ferrite material from the obtained composition.
[0043] The coil 20 includes, for example, a first coil 21 and a second coil 22. The number of coils 20 is not limited to two, and may be only one, or may be three or more.
[0044] 2, the first coil 21 and the second coil 22 are embedded inside the first glass layer 51. The first coil 21 and the second coil 22 are insulated from each other.
[0045] The first coil 21 and the second coil 22 are provided in order in the stacking direction of the element body 10 (here, the height direction T) to form a common mode choke coil.
[0046] The coil 20 including the first coil 21 and the second coil 22 is made of a conductive material such as Ag or Cu. The conductive material constituting the coil 20 is preferably Ag. Thus, the coil 20 preferably contains at least Ag.
[0047] 3, the first coil 21 and the second coil 22 have a spiral pattern wound in the same direction as viewed from the stacking direction (here, the height direction T). The coil 20 including the first coil 21 and the second coil 22 is electrically connected to any one of the external electrodes 30.
[0048] Specifically, one end of the spiral outer periphery of first coil 21 is drawn out to the outer surface of element body 10. The other end of the spiral center of first coil 21 is connected to one end of a first extension conductor 71 through a first via conductor 61 provided inside first glass layer 51, and the other end of first extension conductor 71 is drawn out to the outer surface of element body 10.
[0049] Similarly, one end of the spiral outer periphery of the second coil 22 is drawn out to the outer surface of the element body 10. The other end of the spiral center of the second coil 22 is connected to one end of a second extension conductor 72 through a second via conductor 62 provided inside the first glass layer 51, and the other end of the second extension conductor 72 is drawn out to the outer surface of the element body 10.
[0050] The external electrodes 30 include, for example, a first external electrode 31, a second external electrode 32, a third external electrode 33, and a fourth external electrode 34. The number of the external electrodes 30 is not limited to four (i.e., two pairs) and varies depending on the number of coils 20. Therefore, the number of the external electrodes 30 may be two (i.e., one pair), or may be three or more, for example, six or more (i.e., three pairs).
[0051] The external electrode 30 is electrically connected to the coil 20. In Figures 2 and 3, the first coil 21 has one end drawn out to the outer surface of the element body 10 and connected to the first external electrode 31, and the other end connected to the second external electrode 32 via a first lead conductor 71 drawn out to the outer surface of the element body 10. Similarly, the second coil 22 has one end drawn out to the outer surface of the element body 10 and connected to the third external electrode 33, and the other end connected to the fourth external electrode 34 via a second lead conductor 72 drawn out to the outer surface of the element body 10.
[0052] The external electrodes 30 are present on the outer surface of the element body 10, spanning the first ferrite layer 41, the first glass layer 51 and the second ferrite layer 42. In Fig. 1, the first external electrode 31 and the third external electrode 33 are provided on the first side surface 13a of the element body 10, and the second external electrode 32 and the fourth external electrode 34 are provided on the second side surface 13b of the element body 10. The first external electrode 31, the second external electrode 32, the third external electrode 33 and the fourth external electrode 34 may extend to the first main surface 12a and the second main surface 12b of the element body 10 in a U-shape as shown in Fig. 1.
[0053] As shown in Fig. 1, multiple external electrodes 30 may be present adjacent to each other on one outer surface of the element body 10. In the example shown in Fig. 1, a first external electrode 31 and a third external electrode 33 are present adjacent to each other on a first side surface 13a of the element body 10, and a second external electrode 32 and a fourth external electrode 34 are present adjacent to each other on a second side surface 13b of the element body 10.
[0054] The external electrode 30 includes, for example, a base electrode and a plating electrode provided on the base electrode. The plating electrode may be a single layer or may be two or more layers. The external electrode 30 preferably contains at least Ag.
[0055] When the external electrode 30 includes a base electrode and a plating electrode, the base electrode is preferably a base electrode containing Ag or Cu, and more preferably a base electrode containing Ag. The plating electrode is preferably either one or both of a Ni-plated electrode and a Sn-plated electrode, and more preferably both of a Ni-plated electrode and a Sn-plated electrode. In particular, the external electrode 30 preferably includes a base electrode containing Ag, a Ni-plated electrode provided thereon, and a Sn-plated electrode provided thereon.
[0056] The coil device 1 is manufactured, for example, by the following method.
[0057] <Process for producing glass ceramic material> For example, K 2 O, B 2 O 3 , SiO 2 and Al 2 O 3 are weighed out to a predetermined ratio and mixed in a platinum crucible or the like.
[0058] Next, the mixture is melted by heat treatment at a temperature of, for example, 1500° C. or higher and 1600° C. or lower.
[0059] Thereafter, the resulting melt is quenched to produce a glass material.
[0060] The glass material preferably contains at least K, B and Si, and K is 2 Converted to O, 0.5% by weight or more and 5% by weight or less, B is B 2 O 3 10% by weight or more and 25% by weight or less of Si in terms of SiO 2 70% or more and 85% or less by weight, and Al is2 O 3 It is more preferable that the content is 0% by weight or more and 5% by weight or less in terms of total weight.
[0061] Next, the glass material is pulverized to prepare glass powder. 50 is, for example, 1 μm or more and 3 μm or less. In addition, for example, quartz powder, alumina powder, and forsterite powder are prepared as the filler. The median diameter D of the quartz powder and the alumina powder 50 The median diameter D of the forsterite powder is, for example, 0.5 μm or more and 2.0 μm or less. 90 Here, the median diameter D of the glass powder, the quartz powder, and the alumina powder is set to, for example, 10 μm or less. 50 is the particle size when the cumulative probability based on volume is 50%, and the median diameter D 90 is the particle size when the cumulative probability based on volume is 90%.
[0062] Then, quartz powder, alumina powder, and forsterite powder serving as fillers are added to the glass powder to produce a glass ceramic material (non-magnetic material).
[0063] <Process for producing glass ceramic sheet> The obtained glass ceramic material, an organic binder such as polyvinyl butyral resin, an organic solvent such as ethanol or toluene, a plasticizer, etc. are mixed in a ball mill together with PSZ media to produce a glass ceramic slurry.
[0064] Next, the glass ceramic slurry is formed into a sheet of a predetermined thickness by a doctor blade method or the like, and then punched into a predetermined shape to produce a glass ceramic sheet. The thickness of the glass ceramic sheet is, for example, 20 μm or more and 30 μm or less. The shape of the glass ceramic sheet is, for example, rectangular.
[0065] <Process for producing ferrite material> For example, Fe 2 O 3 ZnO, CuO and NiO are weighed out to give a predetermined ratio. 3 O 4 , Co 3 O 4 , SnO 2 , Bi 2 O 3 , SiO 2 Additives such as the above may also be added.
[0066] Next, these weighed materials, pure water, a dispersant, etc. are placed in a ball mill together with PSZ media, mixed, and then pulverized.
[0067] The resulting pulverized material is dried and then calcined at a calcination temperature of, for example, 700° C. to 800° C. for, for example, 2 hours to 3 hours.
[0068] In this manner, a powdered ferrite material (magnetic material) is produced.
[0069] Ferrite materials are made of Fe 2 O 3 It is preferable that the content is 40 mol% or more and 49.5 mol% or less when calculated as Zn, 5 mol% or more and 35 mol% or less when calculated as ZnO, 6 mol% or more and 12 mol% or less when calculated as CuO, and 8 mol% or more and 40 mol% or less when calculated as NiO.
[0070] <Process for producing ferrite sheets> The obtained powdered ferrite material, an organic binder such as polyvinyl butyral resin, an organic solvent such as ethanol or toluene, etc. are mixed in a ball mill together with PSZ media, and then pulverized to produce a ferrite slurry.
[0071] Next, the ferrite slurry is formed into a sheet of a predetermined thickness by a doctor blade method or the like, and then punched into a predetermined shape to produce a ferrite sheet. The shape of the ferrite sheet is, for example, a rectangular shape.
[0072] <Process for forming conductor patterns> A conductive paste such as Ag paste is applied to a predetermined glass ceramic sheet by a method such as screen printing to form a conductor pattern for a coil conductor corresponding to the first coil 21 and the second coil 22 shown in Fig. 3, a conductor pattern for a via conductor corresponding to the first via conductor 61 and the second via conductor 62 shown in Fig. 3, and a conductor pattern for a lead conductor corresponding to the first lead conductor 71 and the second lead conductor 72 shown in Fig. 3. When forming the conductor pattern for the via conductor, via holes are formed in advance by irradiating predetermined locations of the glass ceramic sheet with a laser, and the via holes are filled with the conductive paste.
[0073] <Step of Producing Laminated Block> For example, the glass ceramic sheets on which the conductive patterns are formed are stacked in the stacking direction (here, height direction T) in the order of glass ceramic sheets 51a, 51b, 51c, and 51d shown in Fig. 3. At this time, as shown in Fig. 3, a glass ceramic sheet 51e on which no conductive pattern is formed is stacked on one main surface in the stacking direction (here, height direction T) of the obtained laminate. Furthermore, although not shown in Fig. 3, a glass ceramic sheet on which no conductive pattern is formed may be stacked on the other main surface in the stacking direction (here, height direction T) of the obtained laminate. The number of glass ceramic sheets on which no conductive pattern is formed is not particularly limited.
[0074] Next, a predetermined number of ferrite sheets are laminated on both main surfaces in the lamination direction (here, the height direction T) of the obtained laminate of glass ceramic sheets. At this time, a first ferrite sheet is laminated on one main surface of the laminate of glass ceramic sheets, and a second ferrite sheet is laminated on the other main surface. For example, as shown in FIG. 3, first ferrite sheets 41a and 41b are laminated on one main surface of the laminate of glass ceramic sheets, and second ferrite sheets 42a and 42b are laminated on the other main surface.
[0075] The resulting laminate of the glass ceramic sheet and the ferrite sheet is then compressed by a warm isostatic press (WIP) process or the like to produce a laminate block.
[0076] <Process for producing element body and coil> First, the laminate block is cut into individual chips of a predetermined size using a dicer or the like.
[0077] Next, the individual chips are fired. The firing atmosphere is preferably a low-oxygen atmosphere. In this case, the oxygen concentration of the firing atmosphere is preferably 5% by volume or less. On the other hand, from the viewpoint of ensuring the sinterability of the ferrite material, the oxygen concentration of the firing atmosphere is preferably 0.1% by volume or more. The firing temperature is, for example, 860°C or more and 920°C or less. The firing time is, for example, 1 hour or more and 2 hours or less.
[0078] In this manner, for example, an element body 10 including a laminate in which a first ferrite layer 41, a first glass layer 51 and a second ferrite layer 42 are stacked in this order, and a coil 20 including a first coil 21 and a second coil 22 embedded inside the first glass layer 51 are produced.
[0079] The corners and ridges of the element 10 may be rounded by, for example, placing the element 10 together with media in a rotary barrel machine and subjecting the element 10 to barrel polishing.
[0080] <Process for forming external electrodes> For example, a conductive paste such as a paste containing Ag and glass frit is applied to at least two locations on the first side surface 13a of the element body 10 and two locations on the second side surface 13b of the element body 10, a total of four locations.
[0081] Next, each of the resulting coating films is baked to form a base electrode on the outer surface of the element 10.
[0082] Then, plating electrodes, for example, a Ni-plated electrode and a Sn-plated electrode, are formed in this order on the surface of each base electrode by electrolytic plating or the like.
[0083] In this manner, external electrodes 30 including base electrodes and plated electrodes are formed on the outer surfaces of the element body 10.
[0084] In this manner, the coil component 1 is manufactured.
[0085] [Second embodiment] In a coil component according to a second embodiment of the present invention, the element body further includes a second glass layer on the outside of the first ferrite layer and a third glass layer on the outside of the second ferrite layer. The second embodiment of the present invention differs from the first embodiment of the present invention in that the element body includes a second glass layer and a third glass layer. Therefore, only configurations different from the first embodiment will be described below. Note that in the second embodiment, the same reference numerals as those in the first embodiment represent configurations in common with the first embodiment, and therefore descriptions thereof will be omitted.
[0086] Fig. 4 is a perspective view showing a schematic example of a coil component according to a second embodiment of the present invention, Fig. 5 is a WT cross-sectional view of the coil component shown in Fig. 4.
[0087] The coil component 2 shown in Figure 4 comprises an element body 10A, a coil 20 (see Figure 5) embedded inside the element body 10A, and an external electrode 30 (see Figure 5) provided on the outer surface of the element body 10A and electrically connected to the coil 20.
[0088] The element body 10A includes a laminate in which a first ferrite layer 41, a first glass layer 51, and a second ferrite layer 42 are laminated in this order. In the example shown in Fig. 4 and Fig. 5, the first ferrite layer 41, the first glass layer 51, and the second ferrite layer 42 are laminated in the height direction T.
[0089] In other words, the element body 10A includes a first glass layer 51, and a first ferrite layer 41 and a second ferrite layer 42 that sandwich the first glass layer 51 in the stacking direction (here, the height direction T). That is, in the stacking direction (here, the height direction T), the first ferrite layer 41 is disposed on one main surface of the first glass layer 51, and the second ferrite layer 42 is disposed on the other main surface of the first glass layer 51.
[0090] The first glass layer 51 has a region 55 (see FIG. 5) in which Cu and Mg coexist.
[0091] The regions 55 in which Cu and Mg coexist are preferably scattered in the first glass layer 51. In Fig. 5, the regions 55 in which Cu and Mg coexist are uniformly scattered in the first glass layer 51, but they may be scattered non-uniformly in the first glass layer 51.
[0092] The size, shape, and the like of the region 55 where Cu and Mg coexist are not particularly limited, but the maximum width of the region 55 where Cu and Mg coexist is preferably 5 μm or less, more preferably 4 μm or less, whereas the maximum width of the region 55 where Cu and Mg coexist is, for example, 0.5 μm or more.
[0093] The region 55 in which Cu and Mg coexist is preferably present near the interface between the first ferrite layer 41 and the first glass layer 51. Specifically, the region 55 in which Cu and Mg coexist is preferably present within a range of 1 / 5 of the thickness of the first glass layer 51 from the interface between the first ferrite layer 41 and the first glass layer 51, for example, within 20 μm from the interface between the first ferrite layer 41 and the first glass layer 51. Similarly, the region 55 in which Cu and Mg coexist is preferably present near the interface between the second ferrite layer 42 and the first glass layer 51. Specifically, the region 55 in which Cu and Mg coexist is preferably present within a range of 1 / 5 of the thickness of the first glass layer 51 from the interface between the second ferrite layer 42 and the first glass layer 51, for example, within 20 μm from the interface between the second ferrite layer 42 and the first glass layer 51. In addition, in a range other than the above, for example, near the center in the thickness direction of the first glass layer 51, a region 55 in which Cu and Mg coexist may or may not be present.
[0094] The element body 10A further includes a second glass layer 52 on the outer side of the first ferrite layer 41, and a third glass layer 53 on the outer side of the second ferrite layer .
[0095] In other words, the element body 10A includes a laminate in which the second glass layer 52, the first ferrite layer 41, the first glass layer 51, the second ferrite layer 42, and the third glass layer 53 are laminated in this order.
[0096] In addition to the first glass layer 51, a region 55 (see FIG. 5 ) in which Cu and Mg coexist may be present in at least one of the second glass layer 52 and the third glass layer 53, but it does not have to be present. The region 55 in which Cu and Mg coexist may be present only in the first glass layer 51, may be present in the first glass layer 51 and the second glass layer 52, may be present in the first glass layer 51 and the third glass layer 53, or may be present in the first glass layer 51, the second glass layer 52, and the third glass layer 53.
[0097] When the region 55 where Cu and Mg coexist is present in the second glass layer 52, the region 55 where Cu and Mg coexist is preferably scattered in the second glass layer 52. In Fig. 5, the region 55 where Cu and Mg coexist is uniformly scattered in the second glass layer 52, but the region 55 may be unevenly scattered in the second glass layer 52.
[0098] When the region 55 where Cu and Mg coexist is present in the second glass layer 52, the size, shape, etc. of the region 55 where Cu and Mg coexist are not particularly limited, but the maximum width of the region 55 where Cu and Mg coexist is preferably 5 μm or less, more preferably 4 μm or less. On the other hand, the maximum width of the region 55 where Cu and Mg coexist is, for example, 0.5 μm or more. The maximum width of the region 55 where Cu and Mg coexist may be the same or different between the first glass layer 51 and the second glass layer 52.
[0099] When the region 55 in which Cu and Mg coexist is present in the second glass layer 52, the region 55 in which Cu and Mg coexist is preferably present near the interface between the first ferrite layer 41 and the second glass layer 52. Specifically, the region 55 in which Cu and Mg coexist is preferably present in a range within 1 / 5 of the thickness of the second glass layer 52 from the interface between the first ferrite layer 41 and the second glass layer 52, for example, within 20 μm from the interface between the first ferrite layer 41 and the second glass layer 52. The region 55 in which Cu and Mg coexist may or may not be present in a range other than the above, for example, near the center in the thickness direction of the second glass layer 52.
[0100] The second glass layer 52 is preferably made of a glass ceramic material containing a glass material and a filler. The glass ceramic material constituting the second glass layer 52 may be the same as or different from the glass ceramic material constituting the first glass layer 51.
[0101] The thickness (dimension in the height direction T) of the second glass layer 52 may be the same as the thickness of the first glass layer 51, or may be different.
[0102] When the regions 55 in which Cu and Mg coexist are present in the third glass layer 53, the regions 55 in which Cu and Mg coexist are preferably scattered throughout the third glass layer 53. In Fig. 5, the regions 55 in which Cu and Mg coexist are uniformly scattered throughout the third glass layer 53, but they may be unevenly scattered throughout the third glass layer 53.
[0103] When the region 55 where Cu and Mg coexist is present in the third glass layer 53, the size, shape, etc. of the region 55 where Cu and Mg coexist are not particularly limited, but the maximum width of the region 55 where Cu and Mg coexist is preferably 5 μm or less, more preferably 4 μm or less. On the other hand, the maximum width of the region 55 where Cu and Mg coexist is, for example, 0.5 μm or more. The maximum width of the region 55 where Cu and Mg coexist may be the same or different between the first glass layer 51 and the third glass layer 53. Also, the maximum width of the region 55 where Cu and Mg coexist may be the same or different between the second glass layer 52 and the third glass layer 53.
[0104] When the region 55 in which Cu and Mg coexist is present in the third glass layer 53, the region 55 in which Cu and Mg coexist is preferably present near the interface between the second ferrite layer 42 and the third glass layer 53. Specifically, the region 55 in which Cu and Mg coexist is preferably present in a range within ⅕ of the thickness of the third glass layer 53 from the interface between the second ferrite layer 42 and the third glass layer 53, for example, within a range of 20 μm from the interface between the second ferrite layer 42 and the third glass layer 53. The region 55 in which Cu and Mg coexist may or may not be present in a range other than the above, for example, near the center in the thickness direction of the third glass layer 53.
[0105] The third glass layer 53 is preferably made of a glass ceramic material containing a glass material and a filler. The glass ceramic material constituting the third glass layer 53 may be the same as or different from the glass ceramic material constituting the first glass layer 51. In addition, the glass ceramic material constituting the third glass layer 53 may be the same as or different from the glass ceramic material constituting the second glass layer 52.
[0106] The thickness (dimension in the height direction T) of the third glass layer 53 may be the same as or different from the thickness of the first glass layer 51. In addition, the thickness of the third glass layer 53 may be the same as or different from the thickness of the second glass layer 52.
[0107] The external electrodes 30 are present on the outer surface of the element body 10, extending across the second glass layer 52, the first ferrite layer 41, the first glass layer 51, the second ferrite layer 42, and the third glass layer 53. In Fig. 4, the first external electrode 31 and the third external electrode 33 are provided on the first side surface 13a of the element body 10A, and the second external electrode 32 and the fourth external electrode 34 are provided on the second side surface 13b of the element body 10A. The first external electrode 31, the second external electrode 32, the third external electrode 33, and the fourth external electrode 34 may extend in a U-shape to the first main surface 12a and the second main surface 12b of the element body 10A, as shown in Fig. 4.
[0108] The coil device 2 is manufactured in the same manner as the coil device 1, except that the <step of producing a laminate block> is carried out as follows, for example.
[0109] <Step of Producing Laminated Block> First, each glass ceramic sheet on which a conductive pattern is formed is laminated in the lamination direction (here, the height direction T). At this time, a glass ceramic sheet on which a conductive pattern is not formed is laminated on one main surface in the lamination direction (here, the height direction) of the obtained laminate. Furthermore, a glass ceramic sheet on which a conductive pattern is not formed may be laminated on the other main surface in the lamination direction (here, the height direction T) of the obtained laminate. The number of glass ceramic sheets on which a conductive pattern is not formed is not particularly limited.
[0110] Next, a predetermined number of ferrite sheets are laminated on both main surfaces in the lamination direction (here, the height direction T) of the obtained laminate of glass ceramic sheets. At this time, a first ferrite sheet is laminated on one main surface of the laminate of glass ceramic sheets, and a second ferrite sheet is laminated on the other main surface.
[0111] Next, a predetermined number of glass ceramic sheets on which no conductive pattern is formed are laminated in the lamination direction (here, height direction T) on the laminated portion of the first ferrite sheet and the laminated portion of the second ferrite sheet.
[0112] The resulting laminate of the glass ceramic sheet and the ferrite sheet is then compressed by warm isostatic pressing or the like to produce a laminate block.
[0113] Thereafter, in the <process of producing element and coil>, individual chips are produced, and then the individual chips are fired.
[0114] The present specification discloses the following:
[0115] <1> an element body including a laminate in which a first ferrite layer, a first glass layer, and a second ferrite layer are laminated in this order; a coil embedded within the first glass layer; an external electrode provided on an outer surface of the element body and electrically connected to the coil; The coil component, wherein the first glass layer has a region in which Cu and Mg coexist.
[0116] <2> the regions in which Cu and Mg coexist are scattered in the first glass layer; <1> The coil component according to claim 1.
[0117] <3> The maximum width of the region where Cu and Mg coexist is 5 μm or less. <1> or <2> The coil component according to claim 1.
[0118] <4> The element further includes a second glass layer on the outer side of the first ferrite layer and a third glass layer on the outer side of the second ferrite layer. <1> ~ <3> 13. The coil component according to claim 12,
[0119] <5> The first glass layer contains at least B, Si and Mg. <1> ~ <4> 13. The coil component according to claim 12,
[0120] <6> The first glass layer contains at least forsterite. <1> ~ <5> 13. The coil component according to claim 12,
[0121] <7> The coil contains at least Ag. <1> ~ <6> 13. The coil component according to claim 12,
[0122] <8> The external electrodes contain at least Ag. <1> ~ <7> 13. The coil component according to claim 12,
[0123] <9> The coil includes a first coil and a second coil, which are common mode choke coils embedded inside the first glass layer. <1> ~ <8> 13. The coil component according to claim 12, EXAMPLES
[0124] Hereinafter, examples of the coil component of the present invention will be described in more detail. However, the present invention is not limited to these examples.
[0125] [Example 1] Borosilicate glass powder, alumina powder, quartz powder, and forsterite powder containing K and Al were prepared. The borosilicate glass powder was weighed out in proportions of 77.5 volume %, alumina powder in proportions of 1.5 volume %, quartz powder in proportions of 11 volume %, and forsterite powder in proportions of 10 volume %, and a glass ceramic sheet was produced by the methods described in the above-mentioned <Step of producing glass ceramic material> and <Step of producing glass ceramic sheet>.
[0126] Fe 2 O 3 The powder, NiO powder, ZnO powder and CuO powder were weighed in a predetermined ratio, and a ferrite sheet was produced by the method described in the above-mentioned <Step of producing ferrite material> and <Step of producing ferrite sheet>.
[0127] A conductor pattern was printed on a specified glass ceramic sheet by the method described above in the <Process for forming a conductor pattern>, and then the glass ceramic sheet was laminated with a first ferrite sheet and a second ferrite sheet on the top and bottom of the glass ceramic sheet, as in Figure 3, and an unsintered laminate (chip) was produced by the procedures described above in the <Process for producing a laminate block> and <Process for producing an element and a coil>.
[0128] The unsintered laminate was sintered in a furnace at 910° C. for 2 hours to produce a sintered laminate. During the sintering, the oxygen concentration in the atmosphere was adjusted to 0.1% by volume.
[0129] A conductive paste containing Ag and glass was applied to the fired laminate at the locations where the external electrodes were to be formed, and the laminate was held at 810°C for 1 minute to form base electrodes. Next, a Ni-plated electrode and a Sn-plated electrode were successively formed on the base electrode by electrolytic plating, to form external electrodes including the base electrode and the plated electrode.
[0130] In this manner, a coil component serving as a sample of Example 1 was produced.
[0131] [Comparative Example 1] A coil component, which is a sample of Comparative Example 1, was produced by the same method as in Example 1, except that a glass ceramic sheet was produced using 0 volume % forsterite powder, 86.1 volume % borosilicate glass powder, 1.7 volume % alumina powder, and 12.2 volume % quartz powder, and that the sintering atmosphere was air.
[0132] [Comparative Example 2] A coil component as a sample of Comparative Example 2 was produced in the same manner as in Example 1, except that the sintering was performed in air.
[0133] In all of the samples of Example 1, Comparative Example 1, and Comparative Example 2, the dimensions of the coil components are length L=0.65 mm, width W=0.50 mm, and height T=0.30 mm.
[0134] [Rating 1] After forming the base electrode, the samples of Example 1, Comparative Example 1, and Comparative Example 2 at the stage before forming the plating electrode were stood so that the longitudinal direction L of the sample was vertical, and the periphery of the sample was hardened with resin. Then, using a grinder, the sample was ground in the longitudinal direction L to a depth where approximately the center of the longitudinal direction L was exposed.
[0135] In the cross section (WT cross section) obtained by polishing, Cu and Mg were mapped by field emission wavelength dispersive X-ray analysis (FE-WDX). FE-WDX was performed using a JEOL JXA-8530F. The analysis conditions are as follows: Accelerating voltage: 15.0 kV Irradiation current: 5×10 -8 A Number of pixels (pixels): 256 x 256 Pixel size: 0.4 (1000x) Dwell Time (acquisition time for one pixel): 40 ms Analysis depth: 1μm~2μm
[0136] From the results of mapping analysis of Cu and Mg, segregation of Cu was confirmed in the chip surface portion near the interface between the ferrite layer and the glass layer in the samples of Comparative Example 1 and Comparative Example 2. Furthermore, no region in which Cu and Mg coexisted was confirmed in the glass layer.
[0137] On the other hand, a region in which Cu and Mg coexist was confirmed in the glass layer in the sample of Example 1. The region in which Cu and Mg coexist was a region with a maximum width of 5 μm or less.
[0138] [Rating 2] For the samples of Example 1, Comparative Example 1, and Comparative Example 2 after the plating electrodes were formed, the vicinity of the external electrodes was observed using a digital microscope (VHX-6000 manufactured by Keyence Corporation).
[0139] In the samples of Comparative Example 1 and Comparative Example 2, plating elongation exceeding 30 μm in length was confirmed.
[0140] On the other hand, in the sample of Example 1, plating elongation exceeding a length of 30 μm was not observed.
[0141] In the samples of Comparative Example 1 and Comparative Example 2, it is believed that the Cu component diffused from the ferrite layer into the glass layer when the unsintered laminate was fired, and then the diffused Cu component migrated to the surface of the laminate when the base electrode was baked, resulting in Cu segregation on the surface portion of the laminate.
[0142] On the other hand, in the sample of Example 1, the Cu component diffused into the glass layer when the unsintered laminate was fired and formed a region in which it coexisted with Mg, which is thought to have inhibited the Cu component from migrating to the surface of the laminate when the base electrode was fired.
[0143] In the first embodiment, Mg is added to the glass layer due to forsterite, but the present invention is not limited to this. For example, MgO may be added as a raw material of the glass material. [Explanation of symbols]
[0144] 1, 2 Coil parts 10, 10A body 11a: first end surface of element 11b: second end surface of element 12a: First principal surface of the body 12b Second main surface of the body 13a First side of the body 13b Second side of the body 20 Coil 21 First coil 22 Second coil 30 External electrode 31 1st external electrode 32 2nd external electrode 33 Third external electrode 34 4th external electrode 41 First ferrite layer 41a, 41b First ferrite sheet 42 Second ferrite layer 42a, 42b Second ferrite sheet 51 First glass layer 51a, 51b, 51c, 51d, 51e Glass ceramic sheet 52 Second Glass Layer 53 Third Glass Layer Region where 55 Cu and Mg coexist 61 First via conductor 62 Second via conductor 71 First lead conductor 72 Second lead conductor L Length direction T Height direction W Width direction
Claims
1. an element body including a laminate in which a first ferrite layer, a first glass layer, and a second ferrite layer are laminated in this order; a coil embedded within the first glass layer; an external electrode provided on an outer surface of the element body and electrically connected to the coil; The coil component, wherein the first glass layer has a region in which Cu and Mg coexist.
2. The coil component according to claim 1 , wherein the first glass layer is dotted with regions in which Cu and Mg coexist.
3. The coil component according to claim 2 , wherein the maximum width of the region where Cu and Mg coexist is 5 μm or less.
4. The coil component according to claim 1 , wherein the element further includes a second glass layer on an outer side of the first ferrite layer, and a third glass layer on an outer side of the second ferrite layer.
5. The coil component according to claim 1 , wherein the first glass layer contains at least B, Si, and Mg.
6. The coil component according to claim 1 , wherein the first glass layer contains at least forsterite.
7. The coil component according to claim 1 , wherein the coil contains at least Ag.
8. The coil component according to claim 1 , wherein the external electrodes contain at least Ag.
9. 9. The coil component according to claim 1, wherein the first coil and the second coil are common mode choke coils embedded inside the first glass layer.
Citation Information
Patent Citations
Laminated lc composite component
JP1999265837A
Common mode noise filter
JP2006319009A
Ceramic laminate component
JP2014232897A
Glass-ceramic-ferrite composition and electronic component
JP2019099400A
Multilayer coil component
JP2019102507A